Introducing anthracene and amino groups into Ln-OFs for the photoreduction of Cr(vi) without additional photosensitizers or cocatalysts. Issue 9 (4th April 2023) - Guo, Wenxiao; Wang, Shufang; Hao, Hongguo; Kong, Xiangjin; Yan, Hui; Zhu, Hongjie; Li, Yunwu; Zhou, Huawei; Zhong, Dichang; Dai, Fangna
Abstract : The stable LCUH-100 was designed and synthesized, by incorporating chromophores into lanthanide MOFs, as a high-efficiency photocatalyst, which can rapidly and efficiently reduce Cr(vi ) under visible-light irradiation and has good cycle stability. Abstract : The utilization of catalysts with high stability and activity for the photoreduction of Cr(vi ) is desirable but has many challenges. Since metal–organic frameworks (MOFs) have unique versatilities and facile structural modulations, we fabricated a stable MOF as a highly efficient photocatalyst by incorporating chromophores into lanthanide MOFs for efficient Cr(vi ) reduction. Subsequently, a novel two-dimensional (2D) layered structural Sm(iii ) MOF (namely LCUH-100, [Sm4 (AAPA)6 (DMA)2 (H2 O)4 ][DMA]3 [H2 O]8, AAPA 2− = 5-[(anthracen-9-yl-methyl)-amino]-1, 3-isophthalate, DMA = N, N ′-dimethylacetamide) with sql topology symbol was constructed by incorporating dinuclear clusters, Sm2 (COO)6 and AAPA 2−, which demonstrated excellent chemical and thermal stability, especially retaining its complete framework in aqueous solutions at a pH range of 2–12 for 24 h. Interestingly, LCUH-100 could efficiently and rapidly photocatalyze the reduction of Cr(vi ) to Cr(iii ) without additional photosensitizers or cocatalysts. In the photoreduction of Cr(vi ), LCUH-100 showed a high rate constant ( k ) of 0.186 min −1 and a high Cr(vi ) reduction rate of 1.67 mgCr(VI) g −1 cata min −1 at pH 2. Furthermore, the photocatalyst LCUH-100 could be reused for 5 cycles without any significant loss of catalytic activity. This work provides a new strategy for the exploitation of stable and efficient catalysts for the photocatalytic reduction of Cr(vi ).